2006
DOI: 10.1097/01.inf.0000183751.75880.f8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Criteria of Tuberculous Meningitis in Human Immunodeficiency Virus-Infected and Uninfected Children

Abstract: The diagnostic criteria for clinical diagnosis of TB meningitis apply to HIV-infected children. However, cranial CT findings in this group may be misleading and delay the diagnosis of TB meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 16 publications
1
43
0
2
Order By: Relevance
“…The values of routinely measured cerebrospinal fluid parameters are almost similar in HIV-positive and negative patients with tuberculous meningitis [26,31,35]. Some studies, however, noted a lower cerebrospinal fluid leukocyte count and a lower protein level in HIV-positive patients [25,33].…”
Section: Cerebrospinal Fluid Findingsmentioning
confidence: 92%
See 2 more Smart Citations
“…The values of routinely measured cerebrospinal fluid parameters are almost similar in HIV-positive and negative patients with tuberculous meningitis [26,31,35]. Some studies, however, noted a lower cerebrospinal fluid leukocyte count and a lower protein level in HIV-positive patients [25,33].…”
Section: Cerebrospinal Fluid Findingsmentioning
confidence: 92%
“…The classical clinical manifestations of tuberculous meningitis such as fever, headache, vomiting, and weight loss occurred in equal frequency in patients with and without HIV infection [30]. Even in a pediatric study, both HIV-infected patients and HIV-uninfected patients with tuberculous meningitis had almost similar clinical manifestations [31]. A Vietnamese study observed, in a comparison to patients with HIV-negative tuberculous meningitis, that HIV-infected patients with tuberculous meningitis were younger in age and were more commonly male.…”
Section: Clinical Features-impact Of Hiv Infectionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, studies from SA report extremely low diagnostic yields by this method. [5] Culture of M. tuberculosis from CSF is similarly an insensitive diagnostic test and as time to positivity is at least 2 weeks, it is too slow to be clinically relevant in guiding treatment initiation in TBM. [3] Measures shown to improve the sensitivity of these microbiological tests, which can easily be implemented in our setting, include analysing large volumes of CSF (≥6 mL is advised), and performing repeated LPs.…”
Section: Definitive Diagnostic Methodsmentioning
confidence: 99%
“…HIV-infected patients may have altered clinical presentations, such as in pathological features, CSF parameters, frequency of infection with MDR-TB and mortality. Hospital-associated mortality was significantly higher in HIV-infected patients (Cecchini et al, 2009;van der Weert et al, 2006;Katrak et al, 2000;Bandyopadhyay et al, 2009). Other studies have found that HIV infection was not associated with mortality rate or altered neurological presentation in TBM, though additional extrapulmonary TB was more likely to occur in HIV-infected patients and may have also affected the survival rate (Faksri et al, 2011a;Thwaites et al, 2005a).…”
Section: Predisposing Risk Factorsmentioning
confidence: 99%